2021
DOI: 10.1016/j.trsl.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of the soluble urokinase plasminogen activator receptor (suPAR) correlates with disease activity in early rheumatoid arthritis and reflects joint damage over time

Abstract: Soluble urokinase plasminogen activator receptor (suPAR) is intensively studied as a biomarker of inflammation and disease outcome in various diseases. In rheumatoid arthritis (RA), suPAR have shown an association with inflammation and swollen joints, but data on suPAR in relation to early disease course and disease progression are lacking. This study investigates the potential of suPAR to predict or reflect disease outcome in early RA. Serum suPAR was measured by enzyme-linked immunosorbent assay at disease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Likewise, increased suPAR levels are also associated with a wide range of diseases and disorders-non-communicable and infectious diseases alike, Figure 4 and Appendix II. So far suPAR has been shown elevated in cardiovascular disease, including stroke, ischemic heart disease, venous thromboembolism, and incident atrial fibrillation (96, 107, 108); type 1 diabetes and diabetic complications (109,110); incident and manifest type 2 diabetes (76,111,112); different types of cancer (see Figure 4 and Appendix II) (15,(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129)(130); rheumatic disease, including rheumatoid arthritis (78,79,131) and systemic lupus erythematosus (22); asthma and chronic obstructive pulmonary disease (132); acute and chronic pancreatitis (115,133); chronic liver disease, including non-alcoholic fatty liver disease and cirrhosis (68,134,135); incident acute kidney injury (136,137) and chronic kidney disease (CKD) (138,139); and dementia (77). As previously mentioned, suPAR is also elevated in infectious diseases caused by v...…”
Section: Like Systemic Chronic Inflammation Supar Is Non-specifically Associated With Multiple Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, increased suPAR levels are also associated with a wide range of diseases and disorders-non-communicable and infectious diseases alike, Figure 4 and Appendix II. So far suPAR has been shown elevated in cardiovascular disease, including stroke, ischemic heart disease, venous thromboembolism, and incident atrial fibrillation (96, 107, 108); type 1 diabetes and diabetic complications (109,110); incident and manifest type 2 diabetes (76,111,112); different types of cancer (see Figure 4 and Appendix II) (15,(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129)(130); rheumatic disease, including rheumatoid arthritis (78,79,131) and systemic lupus erythematosus (22); asthma and chronic obstructive pulmonary disease (132); acute and chronic pancreatitis (115,133); chronic liver disease, including non-alcoholic fatty liver disease and cirrhosis (68,134,135); incident acute kidney injury (136,137) and chronic kidney disease (CKD) (138,139); and dementia (77). As previously mentioned, suPAR is also elevated in infectious diseases caused by v...…”
Section: Like Systemic Chronic Inflammation Supar Is Non-specifically Associated With Multiple Diseasesmentioning
confidence: 99%
“…Likewise, increased suPAR levels are also associated with a wide range of diseases and disorders—non-communicable and infectious diseases alike, Figure 4 and Appendix II . So far suPAR has been shown elevated in cardiovascular disease, including stroke, ischemic heart disease, venous thromboembolism, and incident atrial fibrillation ( 96 , 107 , 108 ); type 1 diabetes and diabetic complications ( 109 , 110 ); incident and manifest type 2 diabetes ( 76 , 111 , 112 ); different types of cancer (see Figure 4 and Appendix II ) ( 15 , 113 130 ); rheumatic disease, including rheumatoid arthritis ( 78 , 79 , 131 ) and systemic lupus erythematosus ( 22 ); asthma and chronic obstructive pulmonary disease ( 132 ); acute and chronic pancreatitis ( 115 , 133 ); chronic liver disease, including non-alcoholic fatty liver disease and cirrhosis ( 68 , 134 , 135 ); incident acute kidney injury ( 136 , 137 ) and chronic kidney disease (CKD) ( 138 , 139 ); and dementia ( 77 ). As previously mentioned, suPAR is also elevated in infectious diseases caused by viruses, bacteria, and parasites, e.g., coronavirus disease 2019 (COVID-19) ( 37 , 140 ), hepatitis B and C ( 135 , 141 ), human immunodeficiency virus (HIV) ( 142 ), bacteremia ( 143 , 144 ), meningitis ( 17 , 145 ), urinary tract infection ( 88 ), pneumonia ( 71 , 146 ), sepsis ( 23 , 147 ), tuberculosis ( 148 ), malaria ( 149 , 150 ), hantavirus ( 151 ), and Crimean-Congo hemorrhagic fever ( 87 ).…”
Section: Properties and Characteristics Indicating That Supar Is A Marker Of Scimentioning
confidence: 99%
“…Apart from urokinase plasminogen activator (uPA, also known as urokinase), uPAR interacts and cooperates with many ligands and receptors, primarily integrins, to facilitate intracellular signalling, cell migration, cell adhesion and tissue remodelling (20). Soluble uPAR (suPAR) results from proteolytic cleavage of uPAR (21), and has gained increased interest as circulating levels are found to reflect severity and prognosticate outcome of several malignant (22)(23)(24)(25)(26), autoimmune (27)(28)(29)(30) and infectious diseases (31)(32)(33)(34)(35)(36)(37). Additionally, suPAR is used in triaging of patients in acute care settings to early predict clinical deterioration due to suspected bacterial infections (38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on biopsies from arthritic lesions in RA patients by in situ zymography revealed pronounced elevations in uPA activity in the hyperproliferative synovial lining ( Busso et al, 1997 ). Accordingly, these lesions express markedly elevated levels of both uPA and uPAR by infiltrating neutrophils, macrophages, and fibroblast-like cells in the inflamed RA synovium ( Almholt et al, 2018 ) and increased plasma levels of soluble uPAR correlate to disease activity ( Slot et al, 1999 ; Enocsson et al, 2021 ).…”
Section: Upar Biologymentioning
confidence: 99%